Power optimization of higher order modulated downlink non-orthogonal multiple access visible light communication - Dwi Astharini; Muhamad Asvial; Dadang Gunawan (Intelligent Systems with Applications, 2025)
Allocation of power is one of the critical aspects of the non-orthogonal multiple access (NOMA) system. On its implementation in higher-order modulation visible light communication (VLC), the consequent constrictions are more problematic. In this paper, power ratio was optimized for NOMA VLC with M-ary pulse amplitude modulation (MPAM). The requirements for user accessibility were chiefly derived from NOMA VLC model and applied to the throughput maximization. The power ratio for each user was then defined using the Karush–Kuhn–Tucker (KKT) optimality conditions, resulting in a suboptimal low-complexity solution for the case of QoS and optimal solution for best-effort scenario. Simulations were conducted to compare the performance between four- and eight-PAM.